Computed tomographic quantitative evaluation of common bile duct size in normal dogs: A reference range study considering body weight - Kim, Yein; Kim, Sung-Soo; Kwon, Danbee; Im, Deokho; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
Common bile duct (CBD) measurements are important for the evaluation of biliary systemic disorders. However, in veterinary medicine, reference ranges for specific body weights (BW) and correlation between CBD diameter and BW have not been studied. This study aimed to establish normal reference ranges of CBD diameter for different BW groups and CBD to aorta ratio (CBD: Ao ratio) which is not affected by BW and to analyse correlation between CBD diameter and BW in normal dogs. CBD diameter was measured at three different sites: porta hepatis (PH), duodenal papilla (DP) level and mid-portion (Mid) between these points using computed tomography (CT) in 263 healthy dogs. The reference range of CBD diameter at PH level: 1.69 ± 0.29 (Class 1; 1kg≤BW<5kg), 1.92 ± 0.35 (Class 2; 5kg≤BW<10kg), 2.08 ± 0.38 (Class 3; 10kg≤BW<15kg), 2.68 ± 0.54 (Class 4; 15kg≤BW<30kg); Mid-level: 2.06 ± 0.25 (Class 1), 2.43 ± 0.37 (Class 2), 2.60 ± 0.42 (Class 3), 3.02 ± 0.53 (Class 4); DP level: 2.33 ± 0.34 (Class 1), 2.90 ± 0.36 (Class 2), 3.20 ± 0.45 (Class 3), 3.70 ± 0.48 (Class 4). There was a significant difference in CBD diameter for most BW groups. Furthermore, BW and CBD diameter showed positive linear correlation at each level. We devised CBD: Ao ratio at each level that showed no significant difference between the different BW groups; PH level: 0.34 ± 0.05; Mid-level: 0.42 ± 0.06; DP level: 0.47 ± 0.06. In conclusion, since the CBD diameter for each BW is significantly different, different normal reference ranges of CBD diameter should be applied for each BW, and the CBD: Ao ratio can be used regardless of the BW.